FUNGSI RITUAL TARI NOPENG DALAM UPACARA ADAT NOTOKNG SUKU DAYAK KANAYATN KECAMATAN SENGAH TEMILAK KABUPATEN LANDAK KALIMANTAN BARAT - rezeki, Sri; Syahrani, Agus; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is to investigate the function of the Nopeng dance ritual in the Notokng traditional ceremony. 1) Describe the Nopeng dance ritual in the Notokng traditional ceremony, 2) Describe the mask form of the Nopeng dance ritual in the Notokng traditional ceremony, 3) Describe the implementation of the research result as the training material on the subject of art and culture. Used the descriptive method with qualitative and etno-choreology approaches with Adrianus Adiran as the source person who has a well understanding of the Nopeng dance ritual in the Notokng traditional ceremony at Senakin village. The result of an in-depth interview, observation, and documentation. Nopeng dance is one of the dance rituals exist among the Dayaknese Kanayatn tribe especially in a Notokng ceremony with the aims to call the ancient spirits and to guard the Notokng ceremony from the evil spirits. The result of this research is expected to be implemented in a Junior High School Art and Culture subject in the grade VII on the second semester.Keywords: Ritual, Masks forms, Nopeng dance